Analysis of PTUN Jakarta Decision Number 99 of 2020 Concerning the Cancellation of the DPR-RI Statement on the Semanggi 1 and Semanggi 2 Incidents in the Terms of Fiqh Siyasah - Hutapea, Riansyah; Irwansyah, Irwansyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
In the Semanggi 1 and Semanggi 2 incidents, serious human rights violations occurred. The DPR-RI decision was then challenged by a number of community organizations to the Jakarta State Administrative Court (PTUN). This study aims to analyze the history of the Semanggi 1 and Semanggi 2 events, analyzing the Jakarta Administrative Court's decision Number 99 of 2020 concerning the cancellation of the DPR-RI statement on the Semanggi 1 and Semanggi 2 events, and terms of Fiqh Siyasah on the Jakarta Administrative Court's decision Number 99 of 2020 concerning the cancellation of the DPR-RI's statement on Semanggi 1 and Semanggi 2. Then this scientific work research uses normative juridical research methods, namely research based on secondary data sources including primary legal materials in the form of laws and regulations (statute approach) and secondary legal sources with library materials, such as books, scientific articles and journals. The results of this study show that in Decision Number 99 of 2020, the Jakarta State Administrative Court annulled the DPR-RI Decision with the consideration that the DPR-RI had made a mistake in assessing the Semanggi I and II events as not being gross human rights violations. Then the Jakarta State Administrative Court Decision Number 99 of 2020 did not emphasize the suitability in the context of fiqh siyasah. In the concept of fiqh siyasah, the decision of the Jakarta State Administrative Court Number 99 of 2020 does not fulfill the principles of Justice (Al-Adl) and Legal Certainty (Al-Yaqin). This research emphasizes the need for fair law enforcement and legal certainty to deal with human rights in Indonesia, especially in the events of Semanggi 1 and 2.